Verbal nouns abstracts with the suffix -imas / -ymas in the catechism of M. Petkevičius (1598): the formation and translation - Smetonienė, Anželika (Lietuvių kalba, 2016)
The catechism of M. Petkevičius (1598) is the first book in Lithuanian language by Reformers in the Grand Duchy of Lithuania, the second book in Lithuanian language in the Grand Duchy of Lithuania and the first hymnal in the Grand Duchy of Lithuania, however, there are only few studies of it. In this article verbal nouns abstracts, derivatives with suffix -imas / -ymas from verbs, are analysed. The aim is to determinate whether such abstract making type in the sixteenth century was most numerous, as is it today, and is some rare type of making such derivative abstracts recorded in the catechism of M. Petkevičius. Also, it was fond what Polish words were translated to Lithuanian language as verbal nouns abstracts. In order to achieve the aim, from the catechism of M. Petkevičius were elected all such abstracts: 220 different abstracts with suffix -imas / -ymas, that was used a total of 780 times. In conclusion it can be said that already in the catechism of M. Petkevičius derivatives from verbs with the suffix -imas / -ymas significantly prevails, although there are recorded a different pattern of verbal abstract derivatives (eg. mėgumas). Moreover, at the end of a sixteenth century the formation of verbal abstracts with suffix -imas / -ymas was established and little different from the formation of such abstracts in the current Lithuanian language. Also, there is some correlation between most numerous verbal noun formation type (-imas / -ymas derivatives) in the Lithuanian language and most numerous verbal noun formation type (-anie, -enie, -cie derivatives) in the Polish language: all Polish nomina actionis with suffixes -anie, -enie, -cie were translated to the Lithuanian language as verbal abstracts with suffix -imas / -ymas.